Menduga Bobot Badan Sapi Bali Jantan Berberat di Atas 500 Kilogram (THE ESTIMATION OF LIVE WEIGHT OF BALI BULLS ABOVE 500 KILOGRAMS) - I Putu Sampurna; I Wayan Batan (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2000)
Menduga Bobot Badan Sapi Bali Jantan Berberat di Atas 500 Kilogram (THE ESTIMATION OF LIVE WEIGHT OF BALI BULLS ABOVE 500 KILOGRAMS)